Study of 189 Cases of Diabetic Retinopathy at CMC Larkana - Depar, Safder Ali Abbassi, Shahid Jamal Siddiqui, Sayed Imtiaz Ali Shah, Abdul Qadir Shaikh,Mohammed Yousuf (Pakistan Journal of Ophthalmology, 2007)
Purpose: To study the frequency, presentation and visual outcome after the management of diabetic retinopathy. Material and Methods: The study was carried out at the Department of Ophthalmology, Chandka Medical College Larkana from September 2003 to March 2006. 361 eyes of 189 patients were included in this study. All patients were known diabetic. After taking careful history, complete ocular examination was carried out. The investigations included blood sugar, ocular B scan and FFA was performed where necessary. Treatment modalities include conservative in non proliferate diabetic retinopathy(NPDR) and laser photocoagulation in clinically significant macular edema(CSME) and proliferative diabetic retinopathy(PDR). Patients with vitreous hemorrhage and tractional retinal detachment require vitreoretinal surgery. Results: Mean age at the presentation was 52 years with a range of 22-75 years. 62.5% of the patients were male and 37.5% female. 91% of the patients presented with bilateral diabetic retinopathy and 9% unilateral among the 189 patients. 205 eyes (57%) presented as non proliferative diabetic retinopathy(NPDR) and 156 eyes (43%) as proliferative diabetic retinopathy(PDR), Clinically significant macular edema (CSME) was seen in 90 eyes with NPDR and 29 eyes with PDR i.e. 119 eyes (33%). Vitreous hemorrhage was seen in 28 eyes (8%) and tractional retinal detachment in 14 eyes (4%). Neovascular glaucoma in 4 eyes (1%). Laser photocoagulation was done in 180 eyes. Visual acuity improved in 54 eyes (30%) remained same in 89 eyes (49.5%) and deteriorated in 37 eyes (20.5%). Conclusion: In this hospital based descriptive study diabetic retinopathy was more frequently seen in male individuals. Non proliferative diabetic retinopathy was more frequent, as compared to proliferative diabetic retinopathy. Laser photocoagulation improved the vision in patients who had no vitreous hemorrhage and tractional retinal detachment.